ANALISIS RESIKO SISTEMATIK SAHAM BIASA YANG DIKELUARKAN DARI LANTAI BURSA : Studi Empiris di Bursa Efek Jakarta - Wibowo, Dodie Setyo (JURNAL BISNIS STRATEGI, 2001)
The aim of this research is to provide an additional empirical evidence to the companies concerning systematical risk effect of general stock issued from the stock exchange at the Jakarta Stock Exchange. It was done by analyzing the financial leverage effect, the stock return standard deviation and the stock return correlation against the market return against the general stock systematical risk, the financial risk, as analyzing differences among the general stock systematical risk, the financial risk, stock return standard deviation, the stock return correlation and the market return of the delisting company as well as the sound company in between.This research used the secondary data, i.e. data relating to monthly stock price (closing price), monthly Composite stock Price Index, Total Asset and Total Debt. This time period of the research was 24 months before the emittens removed from the stock exchange. Population of the study consisted of all emittens at the Jakarta Stock Exchange since 1 January 1994 up to 31 December 2000 include 291 listing and 33 delisting emittens. Sample selection was conducted by utilizing purposive sampling method, and yielding 31 delisting and 31 sound emittens as a standard of comparison.This research’s analytical device was a multiple regression to analyze the influence of independent variables toward dependent variable. Independent sample t-test was used to analyze the differences between the sound and the delisting companies.Based on the research result there was found that the stock return deviation standard and the stock return correlation and the market return affecting the general stock systematical risk significantly. Apart from that there was a significant difference between the sound company’s financial leverage as well as the general stock systematical risk and the delisting company’s.